PENINGKATAN HASIL BELAJAR KOGNITIF IPA MATERI SIKLUS AIR MENGGUNAKAN MODEL DISCOVERY LEARNING SD NEGERI 2 SURABAYA - Dhany, Kenny Rama (Jurnal Analisis Pendidikan Sosial, 2024)
The problem of this research is about the results of learning science on water cycle material for fifth grade students at SDN 2 Surabaya, Padang Ratu District, Central Lampung Regency. The purpose of this research is to improve the learning outcomes of science learning materials on the water cycle in fifth grade elementary school students using the discovery learning model. The method used is a classroom action research method which consists of three cycles. Each cycle consists of stages of planning, implementing actions, observing and reflecting. Collecting data using tests and non-tests. The results showed that the percentage of students' learning outcomes in the first cycle reached 57% of students above the KKM, the percentage of students' learning outcomes in the second cycle reached 81% of students above the KKM, and the percentage of students' learning outcomes in the third cycle reached 94% of students above the KKM.